Visual Quickstart Guide MySQL, Second Edition - Ullman, Larry (Peachpit Press, 2011)
Even if you've never used MySQL before, this Visual QuickStart Guide will have you up and running with the world’s most popular open source database application in no time. In this completely updated edition of our best-selling guide to MySQL, leading technology author Larry Ullman uses his trademark crystal-clear instructions and friendly prose to introduce you to everything that’s new in MySQL. Filled with step-by-step, task-based instructions and loads of visual aids, this book explains how to interact with MySQL using SQL, the language common to all databases. The interface examples show how to use MySQL’s own tools and how to use three popular programming languages (PHP, Perl, and Java). The book covers MySQL versions 3 and 4, as well as everything new in the eagerly anticipated version 5. Along the way, you'll find extensive coverage of MySQL installation, administration, database design, as well as its use with various programming languages, database programming techniques, utilities, advanced MySQL and SQL, and more!